'My little wild fever-struck brother': human and animal subjectivity in Hélène Cixous' Algeria. Issue 4 (20th October 2017) - Andersson, Helen
ABSTRACT: This article examines the place of human and animal subjectivity in two autobiographically informed texts by Hélène Cixous. It takes her view on the word 'human' and the figure of Fips, the dog of the Cixous family, as a point of departure. By thinking through this figure, I argue, Cixous analyses the dehumanizing logic of colonialism and anti-Semitism in Algeria and develops her own response to such kinds of political evils, arguing for human relationality and animal corporeality. The article shows that Cixous' meeting with Fips creates a stigma that, belatedly, breaks through the barrier between herself and the dog; the reopening of the wound takes place in a poetical writing that reveals an intense 'animal humanity' formed by communal suffering, finiteness, and love. The lesson Cixous learns from the memory of Fips the dog is how to become 'better human'. This becoming is also an assault on the false humanism of the colonial project and on racialized social exclusion.